Pelatihan Komik Edukasi Berbasis Web bagi Komunitas Seni Kota Semarang - Wardani, Theodora Indriati; Purwosetiyono, FX. Didik; Pramasdyahsari, Agnita Siska; Setyawati, Rina Dwi (Perkumpulan Kualitama Edukatika Indonesia, 2025)
In the city of Semarang, as it continues to grow into the fifth-largest metropolitan area in Indonesia, various communities have emerged with specific activities aimed at fostering a sense of love and care for the city, particularly in support of its future development. One such group is an art community based in Semarang that creates works dedicated to the city. This art community operates under the organization Hysteria, an art collective originating from Semarang. Within Hysteria, there is a management structure and a network of individuals consisting of painters and art students. However, when it comes to showcasing their work and sharing information in the form of images and texts with the public or those around their working spaces, they still design comics manually. In this digital era, where skills and expertise in communication technology are increasingly necessary, the comics produced by the art community are still typically conventional or manual in nature—drawn and arranged on paper to eventually be printed as comic books. As a result, the information in these comics does not reach a wide audience and requires significant resources in terms of cost, time, and labor to produce the printed versions, leading to inefficiencies. Therefore, it became necessary to find a way for the community members to independently utilize applications to distribute their comics and convey the comic narratives—particularly educational comics—through internet-based websites in a more engaging way. This led to the idea of a community partnership program by providing training on web-based educational comic creation using the Google Sites software application, eliminating the need for printed illustrations, thereby reducing costs, time, and effort, and accelerating the dissemination of information via the internet for the wider network of art communities spread across Semarang.